United Republic of Tanzania Poverty and Human Development Report 2009 - Ministry of Finance and Economic Affairs (Dar es Salaam Mkuki na Nyota Publishers, 2009)
The Poverty and Human Development Report(PHDR)provides a consolidated national analysis of trends in development in Tanzania. PHDR 2009 is the fifth in the series puvlished since 2002.This report marks the end of the first phase of MKUKUTA.It is a key document for reviewing the accomplishments of MKUKUTA and for examining the challenges facing the country.
Keywords: Poverty